2008
DOI: 10.1901/jaba.2008.41-499
|View full text |Cite
|
Sign up to set email alerts
|

Attendance Rates in a Workplace Predict Subsequent Outcome of Employment‐based Reinforcement of Cocaine Abstinence in Methadone Patients

Abstract: This study assessed whether attendance rates in a workplace predicted subsequent outcome of employment-based reinforcement of cocaine abstinence. Unemployed adults in Baltimore methadone programs who used cocaine (N 5 111) could work in a workplace for 4 hr every weekday and earn $10.00 per hour in vouchers for 26 weeks. During an induction period, participants provided urine samples but could work independent of their urinalysis results. After the induction period, participants had to provide urinalysis evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 27 publications
3
57
2
Order By: Relevance
“…Results did not support our primary hypothesis that contingencies placed on drug abstinence and workplace attendance (Abstinence & Work) would produce greater rates of abstinence than no abstinence contingencies. As seen in Table 2 and Figures 1 and 2, participants in this study who were randomly assigned to an Abstinence & Work contingency group were not significantly more likely to abstain from opiates and cocaine when compared to control participants, which is inconsistent with previous studies of employment-based reinforcement that have reported significant differences in drug abstinence between experimental and control groups (Donlin et al, 2008; Silverman et al, 2001; Silverman et al, 2007). …”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Results did not support our primary hypothesis that contingencies placed on drug abstinence and workplace attendance (Abstinence & Work) would produce greater rates of abstinence than no abstinence contingencies. As seen in Table 2 and Figures 1 and 2, participants in this study who were randomly assigned to an Abstinence & Work contingency group were not significantly more likely to abstain from opiates and cocaine when compared to control participants, which is inconsistent with previous studies of employment-based reinforcement that have reported significant differences in drug abstinence between experimental and control groups (Donlin et al, 2008; Silverman et al, 2001; Silverman et al, 2007). …”
Section: Discussioncontrasting
confidence: 97%
“…Previous contingency-based studies that require abstinence from multiple drugs have introduced those contingencies sequentially by requiring participants to achieve abstinence from their primary drug first (e.g., opiates) before introducing abstinence contingencies for secondary drugs (e.g., cocaine). This approach is supported by a meta-analysis that confirmed participants are less successful when they are required to abstain from multiple drugs simultaneously versus sequentially (e.g., Lussier et al 2006), and a previous Therapeutic Workplace study that was able to successful promote abstinence from multiple drugs when those contingencies were introduced sequentially (Donlin et al, 2008). Examination of the data in the current study suggests that the abstinence contingencies may have prevented attendance in the Abstinence & Work group.…”
Section: Discussionmentioning
confidence: 87%
“…While groups did not differ in terms psychiatric severity or homelessness, it is possible that lower functioning individuals were more likely to consistently attend study sessions when provided with reinforcement for attendance, but not when the additional contingency of abstinence was added. Others have found that treatment completion is improved after exposing patients to an initial period of non-contingent reinforcement (37). This and other approaches (e.g., providing higher value rewards, such as housing (38), or adding contingency management to evidence-based treatments for mental illness) might improve treatment retention in this population.…”
Section: Discussionmentioning
confidence: 99%
“…While the cost of delivering contingency management increases when individuals respond to the treatment (they receive more prizes), this increase is modest compared to savings in inpatient care demonstrated in this and other studies (14). While a number of innovative strategies have been explored to provide funding for contingency management reinforcers (e.g., use of donated funds/prizes, opportunities to work) (37), it is likely that contingency management will continue to be underutilized until payers provide funding for the costs of delivering this treatment. An example of this type of reform recently occurred within the Veteran's Administration where contingency management has been approved as a treatment of illicit drug use in veterans receiving intensive outpatient treatment (40).…”
Section: Discussionmentioning
confidence: 99%
“…Participants earned $8.00 per hour in base pay and could earn up to $2.00 more per hour based on their productivity in the computerized training programs. Detailed descriptions of the therapeutic workplace, the web-based training programs, the staffing requirements, and the cost of the intervention can be found elsewhere (DeFulio, Donlin, Wong, & Silverman, 2009; Donlin, Knealing, Needham, Wong, & Silverman, 2008; Knealing, Roebuck, Wong, & Silverman, 2008; Silverman et al, 2007). …”
Section: Methodsmentioning
confidence: 99%